Effect of the Purple Corn Beverage “Chicha Morada” in Composite Resin during Dental Bleaching - Eric Dario Acuña; Leyla Delgado-Cotrina; Francisco Aurelio Rumiche; Lidia Yileng Tay (Scientifica)
During dental bleaching the staining potential of the surface would increase. This study aims to evaluate the staining susceptibility of one bleached composite resin after the exposure to three different beverages: Peruvian purple corn based beverage (chicha morada), green tea, and distilled water. Thirty disk-shaped specimens of one nanofill composite resin were prepared. The specimens were then divided into six groups (n=5): purple corn (P), purple corn + bleaching (PB), green tea (T), green tea + bleaching (TB), distilled water (W), and distilled water + bleaching (WB). In groups that received bleaching, two sessions of bleaching with 35% hydrogen peroxide were done. Following bleaching, specimens were exposed to each liquid thirty minutes daily. Color was measured with a digital spectrophotometer. For statistical analysis, color measurement differences between the obtained results were used: during bleaching, after bleaching, and during + after bleaching. Two-way ANOVA was used to compare the color changes in the resins of all groups (p<0.05). We conclude that all the evaluated beverages produced changes of color in the composite resin regardless of the bleaching procedure. However, purple corn was the only beverage that caused a perceptible color change (ΔE>3.3).